2007
DOI: 10.1088/0022-3727/40/5/012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of impurities on the temperature of an atmospheric helium plasma in microwave resonant cavity

Abstract: The influence of the content and nature of impurities on the rotational temperature of three probe molecules (OH, NH and ) in a helium plasma created in a microwave resonant cavity is investigated by the synthetic spectra method and by mass spectrometry. OH is found to be the only reliable probe to obtain a satisfactory estimation of the gas temperature. In our experimental conditions, depending on the impurity, the gas temperature varies strongly and at 500 ppm, for instance, a difference of 700 K is possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 28 publications
(28 reference statements)
1
38
0
4
Order By: Relevance
“…To estimate the rotational temperature of plasma particles (Trot), we use the measured OH spectra by adopting the fitting method developed by Rodrigo et al [29], and the results are shown in figures 6a and b. As a result, we find that the temperature increases from ~1300 to ~3200 K as the μWP increases from 25 to 200 W (figure 6c).…”
Section: Fig 4 Time Evolution Of the Plasma Length And Bubble Lengthmentioning
confidence: 99%
“…To estimate the rotational temperature of plasma particles (Trot), we use the measured OH spectra by adopting the fitting method developed by Rodrigo et al [29], and the results are shown in figures 6a and b. As a result, we find that the temperature increases from ~1300 to ~3200 K as the μWP increases from 25 to 200 W (figure 6c).…”
Section: Fig 4 Time Evolution Of the Plasma Length And Bubble Lengthmentioning
confidence: 99%
“…In our case, OH(A-X) emission was detected in the emission spectrum of GIWs (see Figure 11). A representative experimental rotational structure of this molecule is given in Figure 13 (black color), which was fitted with the corresponding synthetic rotational spectrum (red dots) that was produced with a home-made code [6,14,15,51]. T rot was obtained as the value giving the best fit between these two spectra based on the least squares method.…”
Section: Optical Emission Characteristics Of Giwsmentioning
confidence: 99%
“…The gas temperature was estimated by recording the rotational distributions of selected bands of the Second Positive System (SPS) of the N 2 molecules and fitting on them the theoretical distributions corresponding to different temperatures by means of homedeveloped software [39]. Moreover, the temperature on the grounded grid was recorded in real-time by attaching a thermocouple (K-type) on its rear surface and reading the data with a data logger.…”
Section: Analysis Of Plasma Reactive Speciesmentioning
confidence: 99%